2023
DOI: 10.1021/acsaem.3c00764
|View full text |Cite
|
Sign up to set email alerts
|

RuO2 Nanostructure as an Efficient and Versatile Catalyst for H2 Photosynthesis

Abstract: Photocatalytic H2 generation holds promise in the green production of alternative fuels and valuable chemicals. Seeking alternative, cost-effective, stable, and possibly reusable catalysts represents a timeless challenge for scientists working in the field. Herein, commercial RuO2 nanostructures were found to be a robust, versatile, and competitive catalyst in H2 photoproduction in several conditions. We employed it in a classic three-component system and compared its activities with those of the widely used p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Since the pioneering study of photocatalysis using TiO 2 by Fujishima and Honda, Inoue et al used semiconductor powder TiO 2 photocatalytic and electrocatalytic reduction of CO 2 . So far, various types of semiconductor catalysts have been studied for photocatalytic hydrogen production and CO 2 reduction. However, the photocatalytic performance of TiO 2 is still unsatisfactory due to its low utilization efficiency of photogenerated electron–hole pairs, so it is essential to improve the photocatalytic performance of TiO 2 . The investigation found that the photocatalytic performance of TiO 2 has been improved through nanostructure design, , cocatalyst doping, , defect control, , and heterojunction preparation …”
Section: Introductionmentioning
confidence: 99%
“…Since the pioneering study of photocatalysis using TiO 2 by Fujishima and Honda, Inoue et al used semiconductor powder TiO 2 photocatalytic and electrocatalytic reduction of CO 2 . So far, various types of semiconductor catalysts have been studied for photocatalytic hydrogen production and CO 2 reduction. However, the photocatalytic performance of TiO 2 is still unsatisfactory due to its low utilization efficiency of photogenerated electron–hole pairs, so it is essential to improve the photocatalytic performance of TiO 2 . The investigation found that the photocatalytic performance of TiO 2 has been improved through nanostructure design, , cocatalyst doping, , defect control, , and heterojunction preparation …”
Section: Introductionmentioning
confidence: 99%